2018
DOI: 10.1016/j.apmr.2017.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Botulinum Toxin A for Persistent Upper Limb Pain After Breast Cancer Treatment: A Double-Blinded Randomized Controlled Trial

Abstract: A single BTX-A infiltration in combination with an individual physical therapy program significantly decreased pain intensity at the upper limb in breast cancer survivors up to 6 months. However, the effect size was not clinically relevant, and no other beneficial effects were found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 45 publications
2
36
1
Order By: Relevance
“…This is the first randomized controlled trial investigating the effectiveness of BTX-A on upper limb impairments and dysfunctions after breast cancer. Despite the beneficial effects on pain intensity reported in a previous study (De Groef et al, 2018), no significant nor clinically relevant differences were found between groups. For the first outcome parameter 'shoulder mobility' improvements in both groups were found, in particular for forward flexion ROM.…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…This is the first randomized controlled trial investigating the effectiveness of BTX-A on upper limb impairments and dysfunctions after breast cancer. Despite the beneficial effects on pain intensity reported in a previous study (De Groef et al, 2018), no significant nor clinically relevant differences were found between groups. For the first outcome parameter 'shoulder mobility' improvements in both groups were found, in particular for forward flexion ROM.…”
Section: Discussioncontrasting
confidence: 87%
“…As indicated in previous studies, pain and upper limb impairments are complex and difficult to treat. (De Groef et al, 2018, De Groef et al, 2015, De Groef et al, 2017a, De Groef et al, 2017c, De Groef et al, 2017d Similar as in these previous studies it appears that a certain subgroup of patients responds well to the intervention while others do only partly or not at all. An individually tailored approach is needed to increase effectiveness of the applied physical therapy modalities and other interventions such as BTX-A.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations